EFFECTS OF IONIZING RADIATION ON THE HUMAN BODY AND MODERN PROTECTION STRATEGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In the modern era of technological progress, radiation has become an integral part of human life. It is widely used in medicine, energy production, and industry, playing a key role in disease diagnosis and treatment, electricity generation, and scientific research. However, when exposure is uncontrolled or safety standards are violated, radiation poses a serious threat to human health and the environment. This work examines the nature and sources of radiation, the mechanisms of its interaction with living tissues, and the biological effects that arise from exposure. Special attention is given to modern methods of radiation protection, including engineering, medical, and organizational approaches. Based on scientific data and analysis of real cases, it is shown that radiation is a double-edged force: on one hand, a powerful tool that saves lives and contributes to human progress, and on the other hand, a potentially lethal factor when handled carelessly. Thus, the key task of modern society is the responsible and safe use of radiation technologies in the interest of health and sustainable development.